The Analysis of Financial Innovation in Enhancing the Green Economic Transition at PT. Astra Argo Lestari Tbk - Sihaloho, Yolanda Maghdalena; Sabrina, Celine Amanda Sarifatul; Misel, Rheinata Audreyna; Pandin, Maria Yovita. R (Universitas Indo Global Mandiri Palembang, 2024)
Objective: The author's objective in writing this article is to analyze the implementation of financial innovations at PT. Astra Argo Lestari Tbk in supporting the transition towards a green economy over the past three years. Method: This study employs descriptive-qualitative research to investigate a specific event. Results: In 2021, the company took progressive steps in developing innovations and technologies to strengthen its operations. In 2022, the company committed to consistently exploring and leveraging the best opportunities for its advancement. In 2023, the company continued to advance Astra Agro's sustainability vision by setting achievement targets aimed at 2030, in line with its sustainability commitments. Originality/Value: This article asserts that financial innovation plays a crucial role in accelerating the transition to a green economy at PT. Astra Agro Lestari Tbk. The company has utilized modern financial instruments to design a green economic transition, which resulted in profit increases in 2021-2022. Despite experiencing a profit decline in 2022-2023, the company continues to enhance digitalization programs to improve business efficiency in support of sustainability goals by 2030.